2018
DOI: 10.1088/2043-6254/aae989
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibiofilm and catalytic activity of biogenic silver nanoparticles synthesized from Acacia nilotica leaf extract

Abstract: In the current research of bacteriology, the biofilm infections are becoming serious issues. The biofilm has potential resistant towards antibiotics, even at higher concentration, due to the protective covering that enable unavailability of these antibiotics towards bacteria residing inside. Thus to combat these problems, biogenic silver nanoparticles (AgNPs) of spherical shape were synthesized having potential against biofilm forming bacteria. Here, we focused on the green synthesis owing to its inherent feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…A similar study done by Arya et al indicated that AgNPs prepared using aqueous leaf extract of Acacia nilotica inhibited biofilm formation by 70% and 53% in Pseudomonas aeruginosa and Staphylococcus aureus respectively at a concentration of 0.25 µg (Arya et al, 2018).…”
Section: Silver Nanoparticlessupporting
confidence: 54%
“…A similar study done by Arya et al indicated that AgNPs prepared using aqueous leaf extract of Acacia nilotica inhibited biofilm formation by 70% and 53% in Pseudomonas aeruginosa and Staphylococcus aureus respectively at a concentration of 0.25 µg (Arya et al, 2018).…”
Section: Silver Nanoparticlessupporting
confidence: 54%
“…Although several medicinal plant extracts containing different reducing agents, such as phenolic, polyphenol, and flavonoid compounds, have been widely applied for the green synthesis of AgNP [10][11][12], there are few reports on the use of F. asafoetida and its natural constituents for the biosynthesis of AgNPs. Ferula asafoetida contains many natural metabolites, including proteins, polysaccharides, alkaloids, and alcoholic compounds, which can act as reducing agents and exert beneficial biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Different types and parts of a plant such as Prosopis juliflora bark, Prosopis juliflora leaf, Cicer arietinum leaves, Trigonella foenum-graecum seed, Terminalia chebula fruit, Saraca indica flower, Punica granatum peel, Acacia nilotica leaf, etc. have been used for biosynthesis of sAgNPs [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Not only the plant parts but the waste from the plants have also been explored for the biosynthesis of AgNPs, such as lignin extracted from wheat straw and grape pomace from the wine industry [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%